2013
DOI: 10.1515/polyeng-2013-0048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of compatibilizing agents on the physical properties of iPP/HDPE organoclay blends

Abstract: Abstract Blends of isotactic polypropylene (iPP) and high density polyethylene (HDPE), with and without compatibilizers and with different organoclay amounts (1%, 3%, and 5%), were systematically investigated to assess the effect of the additives on the crystallinity of the blends, as well as the correlation between the microhardness, H and the Young’s modulus E. The compatibilizers used were: maleic anhydride grafted styren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…When observing this phenomenon, it was found that the obtained peaks came from the introduced compatibilizer, which was polyethylene grafted with maleic anhydride. The obtained band corresponds to the literature values for PE (2θ = 21.7°) [ 41 ].…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…When observing this phenomenon, it was found that the obtained peaks came from the introduced compatibilizer, which was polyethylene grafted with maleic anhydride. The obtained band corresponds to the literature values for PE (2θ = 21.7°) [ 41 ].…”
Section: Resultssupporting
confidence: 81%
“…On the WAXS curves of the obtained composites, a wide peak with a 2θ value of about 18° was observed, which is a characteristic result for the arrangement of the PC/ABS polymer [ 41 ]. In addition, the PC/ABS/3%B composite is characterized by small 2θ peaks of approximately 2.9° and 6.2°, while the analysis of the results obtained for fillers revealed that the filler B has a band at 5°.…”
Section: Resultsmentioning
confidence: 99%
“…Microhardness H was determined at room temperature with a Leitz (Wetzlar, Germany) microindentation tester with a square-based diamond indenter. The H value was derived from the residual projected area of indentation according to the following expression [23]:…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in preceding investigations we have examined the influence of a compatibilizer on the morphology and microhardness of iPP/PET /Mmt 15 and iPP/HDPE/compatibilizers and clay. 16 Therefore, our contribution aims to improve the compatibility of hybrid composite materials consisting of a mixture of two initially incompatible polyolefin (PP/HDPE) and particulate nano-filler (CaCO 3 ) treated on the surface with two coupling agents, namely: (organosilane sold under the name Silquest A-172 and organozirconate marketed under the reference Ken-React NZ-12). The aim is to study the relationships between morphology and the mechanical and thermal properties of composites by means of microhardness indentation in combination with DSC and WAXS.…”
Section: Introduction *mentioning
confidence: 99%